Utilização de antena fractal de microfita em projetos de estruturas eletricamente pequenas e independentes da frequência - Ribeiro, Daniel Luiz (2016)
Fractal Antennas are radiating structures generated recursively from the reiterated application of a generating array, having the remarkable feature of being self similar. They are based on the theory of fractal developed by Mandelbrot and whose application is present in almost every branches of science. Such antennas have many applications today, from cell phones to satellite antennas, and have proved to be an attractive alternative for applications that required multiband characteristic associated with high gain and miniaturization. This paper aims do present systematically the basic theory involving fractal antennas, and is based not only on the pioneering contributions of researchers around the world, but also the basic theory of antennas, from which is possible to reach important formulations in the area. Besides the extensive bibliography, was used the computational tool HFSS by Ansoft®, a software that simulates high frequency structures. This program is used to simulate a fractal microstrip antenna proposed by the author, and the results are analyzed, having a dual propose: to exemplify the use of fractal antenna on the one hand, and providing a prototype which could possible be used in special applications, for some designer of antennas. The main fundamental parameters of antennas are analyzed, such as Return Loss, VSWR, Gain, etc., but special emphasis will be given to the application of fractal microstrip structures in two kinds of applications: electrically small antennas and frequency independent antennas.